APLIKASI ‘JAJANANKU’ SEBAGAI SISTEM INFORMASI JAJANAN TRADISIONAL SE-KARESIDENAN KEDU BERBASIS ANDROID BERDASARKAN KAJIAN FOLKLOR - Nugroho, Arif (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2019)
ABSTRACT This research aims at explaining the variety of visible tidbits and describing the mechanism of the said application’s prototype as an information system of traditional tidbits in the area of Kedu in android platform. This research is of Research and Development (R&D) type with descriptive qualitative technique. The target of this research is to optimally utilize the Jajananku application as an information system of traditional tidbits in the area of Kedu in android platform based on folklore study. There are three conclusions deducted from this research. First, there are fifty visible traditional tidbits studied in folklore base and are available in the Jajananku application. Second, the mechanism of the Jajananku application can be easily operated as its design plot has met the research’s target. Third, this application can be accessed in android platform starting from Ice Cream Sandwich (ICS) sdk (software development kit) with 7MB in size containing information abaut traditional tidbits based on folklore study. Keyword: application, information system, traditional tidbits, android, folklore study